2006
DOI: 10.1007/s10452-006-9057-z
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton assemblages in two reservoirs: one subjected to accentuated water level fluctuations, the other with more stable water levels

Abstract: The abundance, composition and dynamics of zooplankton were followed in two reservoirs of the River Douro catchment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
3
16
0
1
Order By: Relevance
“…This finding agrees with previous studies focused on zooplankton communities in highly fluctuating environments (Geraldes and Boavida, 2007). Strong flood events during the spring season are the main drivers that notably favour the dominance of rotifers in the water column.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding agrees with previous studies focused on zooplankton communities in highly fluctuating environments (Geraldes and Boavida, 2007). Strong flood events during the spring season are the main drivers that notably favour the dominance of rotifers in the water column.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, a plausible explanation for the absence of correlations in our study may be that the effect of the high flood events in the middle of spring is so strong that the other effects are being masked. There has been evidence that when a water body is characterized by pronounced water fluctuations, those zooplankton organisms with specific, adaptive advantages will dominate the community (Schmid-Araya and Zuñiga, 1992;Bledzki and Ellison, 2000;Geraldes and Boavida, 2007). Several features, including life-history traits and feeding mechanisms, have been pointed out.…”
Section: Discussionmentioning
confidence: 99%
“…Zooplankton abundance, population dynamics, and assemblage composition are all affected by several physical and chemical factors, which are largely influenced by waterlevel fluctuation (Wetzel 2001;Geraldes and Boavida 2007). We observed an increase in the total zooplankton density as well as the density of several individual taxa À similar to a nearby reservoir during a drought-related drawdown (Olds et al 2014) À that could have resulted from the increase in Chl-a concentration (as a measure of phytoplankton biomass).…”
Section: Zooplankton Assemblagementioning
confidence: 99%
“…Studies were selected from a Biological Abstract search of articles published from 1999 through 2007 in peer-reviewed journals with the phrase "zooplankton density" in the topic search field. Gonzalez et al 2002;Ferrara et al 2002;Bonecker and Aoyagui 2005;Geraldes and Boavida 2007 Not reported 3 Ha et al 2003;Gophen 2003;Sharma and Bhattarai 2005 Total 23 until at least 500 individuals were counted. Biomass estimates dry weight) were obtained using published length-mass estimates (Dumont et al 1975, Downing andRigler 1984).…”
Section: Chick Et Almentioning
confidence: 99%
“…In the 1970s, several studies demonstrated that mesh sizes commonly used to sample crustacean zooplankton (e.g., ≥ 63 µm) underestimate the abundance of rotifers, and recommended mesh sizes ≤ 35 µm for quantitative sampling of rotifers (Likens and Gilbert 1970;Bottrell et al 1976;Ejsmont-Karabin 1978). Despite these recommendations, many studies still report quantitative estimates of rotifer density or biomass based on samples filtered through mesh sizes > 35 µm, including mesh as large as 63 to 80 µm (Bonecker and Lansac-Toha 1996;Ghadouani et al 1998;Shurin 2000;Strecker et al 2004;Geraldes and Boavida 2007). To illustrate the extent of this problem, we used Biological Abstracts BIOSIS to search for articles published from 1999 through 2007 in peer-reviewed journals with the phrase "zooplankton density" in the topic search field.…”
mentioning
confidence: 99%